Analisis Rasio Keuangan APBD untuk Menilai Kinerja Keuangan Daerah Kota Medan Tahun 2016-2020 - Anggi Amelia Silitonga Anggi (Akuntansi Prima, 2022)
Since the enactment of Law No. 22 of 1999, regarding the implementation ofregional autonomy, there will be a fundamental change in regional financial management. Regional autonomy is the authority possessed by an autonomous region to regulate and manage its people according to their own will based on the aspirations of the community, in accordance with the applicable laws and regulations. To assess the performance of the Regional Government in managing their regional finances, among others, by conducting a financial ratio analysis on the local government's financial statements. This study aims to describe the financial performance of the Medan City Government by using the analysis of the Decentralization Degree Ratio, Regional Financial Dependence Ratio, Original Income Effectiveness Ratio, and PAD Efficiency Ratio. This research is a qualitative descriptive study with the object being studied is data on the Realization Report of the Medan City Regional Revenue and Expenditure Budget for the 2016-2020 Fiscal Year. Data collection methods used, observation, and documentation. The results of the research from 2016-2020 show that the Decentralization Degree Ratio obtained an average of 36.90% (enough), the Regional Financial Dependence Ratio obtained an average of 46.72% (high), the Original Income Effectiveness Ratio obtained an average of 81 .36% (less effective), the PAD Efficiency Ratio obtained an average of 11.79% (Efficient).